PENGARUH KEBIJAKAN OPERASIONAL DAN KEPUTUSAN PENDANAAN TERHADAP KUNERJA KEUANGAN PADA PT ALBA PUTRA JOMBANG - Buniarto, Edwin Agus (Universitas Nusantara PGRI Kediri, 2016)
The aims of this study is to examine the financial performance in PT Alba Putra Jombang Resident. This study used data from financial statement of the PT Alba Putra Jombang Resident this study also used 36 month financial statement as the sample. Field research was applied, data collection uses documentation technique. There is one statistical analysis used in this study, that is double regression linier with SPPS software. This study is used to analyse three variables, those are Operational Policy, Capital structure and financial performance.. The result of this study found that operational Policy and capital structure influence to financial performance of the firm during 2013 – 2015. The result also show that financial structure influence financial performance more than operational Policy is influencing financial performance.